Characteristic of Dissolved Organic Matters Removal from Bio-Treated Effluents of Textile and Dyeing Wastewater by Coagulation Enhanced with KMnO4 - Li1, Mu; Sun1, Xianbo; Qian1, Feiyue; Xu1, Hongyong; Liu1, Yongdi (Asian Journal of Chemistry, 2013)
In this paper, the effectiveness of coagulation enhanced with KMnO4 for removal of dissolved organic matter from bio-effluent of textile and dyeing wastewater was investigated. Under the optimal dosing conditions, coagulation enhanced with KMnO4 had better American Dyeing Manufactures Institute value (ADMI7.6) and removal of dissolved organic carbon (83 % versus 72 %; 40 % versus 36 %) than magnesium sulphate coagulation alone. The results of XAD-8/XAD-4 tandem resin fractionation and molecular weight distribution measurements demonstrated that the removal of hydrophobics, transphilics and large-molecular weight organics were improved by enhanced coagulation, the ADMI7.6 value was 40 % lower than the effluent of magnesium sulphate coagulation alone. Moreover, the hydrophilics and low-MW (< 1 K Da) organics in the effluent of enhanced coagulation were increased by 39 and 145 %, respectively, which were the main reasons for inconspicuous improvement of dissolved organic carbon removal. Qualitative analysis on dissolved organic matter with three-dimensional excitation emission matrix fluorescence spectroscopy (3-DEEMs) indicated that the colour-caused matters, fulvic-like and humic-like organics were further removed during enhanced coagulation process. Meanwhile, the increased low-molecular weight hydrophilics were protein-like and fulvic-like organics dominantly. Coagulation enhanced with KMnO4 should be combined with additional treatment steps that specialized in removing the remained dissolved organic matter (mostly molecular weight < 1 K Da, hydrophilic) to produce a high removal performance.